Anesthesia and Surgical Considerations in Awake Craniotomy for Eloquent Area Tumor - Masoudifar, Mehrdad; Mirhosseini, Maryam; Najafabadipour, Amirhossein (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: Awake craniotomy is a specialized neurosurgical technique in which the patient remains conscious during surgery, enabling real-time functional mapping of the cerebral cortex. This procedure is primarily employed when a brain tumor or lesion is situated near critical areas responsible for motor, visual, or language functions. Its application minimizes the risk of postoperative neurological deficits, ensuring the preservation of vital brain functions. Objective: The objective of this case report is to highlight the use of the awake craniotomy technique for a patient with a brain tumor located in the left parietal lobe, emphasizing the surgical and anesthetic considerations necessary for successful outcomes. Case Report: The patient, diagnosed with a brain tumor in the left parietal lobe, presented unique surgical challenges due to the tumor's proximity to the cortical centers governing movement and speech. To mitigate the risk of neurological impairment, an awake craniotomy was performed. Bilateral scalp nerve blocks were administered for effective pain management, alongside dexmedetomidine to provide conscious sedation. The